ONLINE BUYING INTENTIONS OF SHOPEE CONSUMERS: THE INFLUENCE OF CELEBRITY ENDORSEMENT, SOCIAL MEDIA MARKETING, AND BRAND IMAGE - Muhammad Harda Dimas Firmanza; Yessy Artanti (Institute of Research and Community Outreach - Petra Christian University, 2022)
The development of increasingly modern technology has impacted human civilization and changed consumer behavior related to online shopping intentions. Online shopping applications change consumer behavior from consensually purchasing products to digitally downloading them. Technology in the economic field is designed to make it easier for potential consumers to shop online, which is considered more effective and efficient during the COVID-19 pandemic. This study aimed to analyze celebrity endorsements, social media marketing, and the brand image of online shopping intentions of Shopee consumers. This study focuses on potential Shopee users aged 18–65 using non-probability sampling. Data were collected using online questionnaires and analyzed using the multiple linear regression method. The study's results showed that celebrity endorsement and social media marketing had an insignificant influence on the online buying intentions of Shopee consumers (p = 0.018 and p = 0.000). Meanwhile, the brand image does not significantly influence the online buying intentions of Shopee consumers (p = 0.085). Companies must develop promotional strategies with up-to-date product and service performance upgrades to increase online purchase intentions.